Site-specific attachment of Anodonta anatina (Bivalvia: Unionidae) glochidia on two new fish hosts translocated in Lake Trasimeno (Italy) - Ahnelt Harald; Leister Tobias; Kruckenhauser Luise; Duda Michael; Carosi Antonella; Lorenzoni Massimo (Knowledge and Management of Aquatic Ecosystems, 2023)
To complete their life cycle, freshwater mussels of the order Unionida depend on fishes as hosts for their obligatory parasitic larval phase, the glochidium. Here we report the first documentation of gobioid fishes as hosts of glochidia of unionid mussels in the wild in Italy and in southern Europe (outside of the Danube drainage area). We also examined the pattern of the attached glochidia. A recent review reported 326 fish species as suitable hosts for unionids, but only eight (2.5%) of these were Gobioidei. Host identification and the documentation of their benefits or threats for the interaction of the mussels with their hosts is important for conservation of freshwater mussels. But the co-existence of mussels with non-native fish species is only poorly understood, including the compatibility of these two groups. Knipowitschia panizzae and Pomatoschistus canestrinii, two translocated sand gobies, were sampled in 2022 at the east shore of Lake Trasimeno (Italy). Two species of anodontine mussels were present at this locality, the native Anodonta anatina and the translocated Sinanodonta woodiana. Genetic data revealed that both sand gobies hosted glochidia only of A. anatina but not of S. woodiana, possibly because of seasonal bias. About 50% of the specimens of both fish species were infested. The paired fins were the most prominent targets. The examined individuals of both sand gobies carried only few glochidia (max. 5). Nevertheless, the two species showed a divergent pattern of glochidia attachment.